The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12889-019-8058-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring issues in caregivers and parent communication of sexual and reproductive health matters with adolescents in Ebonyi state, Nigeria

Abstract: Background: Parent-child communication is an effective tool for fostering healthy sexual and reproductive behaviours among adolescents. However, the topic is underexplored in Nigeria. This study examines how parents and caregivers communicate sexual and reproductive health-related matters with adolescents aged 13-18 years in Nigeria. Method: The study was undertaken in six communities in Ebonyi state, Nigeria using quantitative and qualitative research methods. Data were collected through, i) cluster randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 19 publications
6
51
0
5
Order By: Relevance
“…In B-GAP we found that older adolescents (16-18 years) were less likely to be tested when compared to children aged 2-5 years (under review). As highlighted by this and previous studies, engaging adolescents is challenging and index-linked testing may expose sexual activity of adolescents to their caregivers [27,28]. As highlighted by caregivers, respecting adolescents' autonomy and approaching them directly and then their caregivers for consent may be more appropriate.…”
Section: Discussionmentioning
confidence: 84%
“…In B-GAP we found that older adolescents (16-18 years) were less likely to be tested when compared to children aged 2-5 years (under review). As highlighted by this and previous studies, engaging adolescents is challenging and index-linked testing may expose sexual activity of adolescents to their caregivers [27,28]. As highlighted by caregivers, respecting adolescents' autonomy and approaching them directly and then their caregivers for consent may be more appropriate.…”
Section: Discussionmentioning
confidence: 84%
“…The state has three senatorial zones with thirteen local government areas. It has 5,533 km 2 estimated land area and more than 40% of its total population are below 15 years of age [17]. The state has an estimated annual growth rate of 2.7% and its adolescents' population is projected to double by year 2050 [17].…”
Section: Study Design and Study Areamentioning
confidence: 99%
“…It has 5,533 km 2 estimated land area and more than 40% of its total population are below 15 years of age [17]. The state has an estimated annual growth rate of 2.7% and its adolescents' population is projected to double by year 2050 [17]. It has been reported that the state has high maternal mortality rate (602 per 100,000 population), and 39.7% of these mortalities occur among adolescent girls age 15-19 years [24][25][26].…”
Section: Study Design and Study Areamentioning
confidence: 99%
See 2 more Smart Citations